“Ho sondato gli abissi del popolo più onesto”. Il Simposio internazionale L’antropologia di Dostoevskij. L'uomo come problema e oggetto di rappresentazione nel mondo di Dostoevskij (ENTHYMEMA, 2019)
From October 23 to 26 of last year eminent scholars, specialists of Dostoevsky, met in Sofia for the «International Symposium: Dostoevsky’s Anthropology. The man as a problem and object of representation in the world of Dostoevsky», a conference organized at Sofia University “St. Kliment Ohridski” by the Bulgarian Dostoevsky Society and by the Institut for Literature of the Bulgarian Academy of Sciences.
Keywords: Bulgarian Dostoevsky Society; Institut for Literature of the Bulgarian Academy of Sciences; International Symposium «The anthropology of Dostoevsky. The man as a problem and as a subject of reflection in Dostoevsky’s world»